2020
DOI: 10.3390/cancers12082065
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Landscape of Epstein–Barr Virus Associated Pulmonary Lymphoepithelioma-Like Carcinoma Revealed by Genomic Sequencing

Abstract: Pulmonary lymphoepithelioma-like carcinoma (LELC) is a subtype of non-small cell lung cancer (NSCLC) characterized by marked lymphocytic infiltration and association with Epstein–Barr virus (EBV). The molecular basis underlying the disease remains unclear. We sought to study the molecular landscape by multiple approaches including whole genomic sequencing, capture-based targeted sequencing, fluorescent in situ hybridization and immunohistochemistry. Tumor cells from 57 EBV-positive pulmonary LELCs were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 53 publications
5
34
0
Order By: Relevance
“…Similar to previous studies by Hong et al and Xie et al, 11,12,37 TP53 mutation was also detected in our study. Except for TP53, no other common FMGs were observed within these studies, but a variety of similar CNVs were identified at both the segment and gene levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to previous studies by Hong et al and Xie et al, 11,12,37 TP53 mutation was also detected in our study. Except for TP53, no other common FMGs were observed within these studies, but a variety of similar CNVs were identified at both the segment and gene levels.…”
Section: Discussionsupporting
confidence: 93%
“…7 However, the prognostic significance of PD-L1 expression in pLELC is still completely controversial [8][9][10] In recent years, a few studies have reported the mutational landscape of pLELC using multiple approaches, including wholeexome sequencing, targeted deep sequencing, and singlenucleotide polymorphism (SNP) arrays. 11,12 However, analysis at the RNA level, e.g., transcriptome sequencing, seems to be absent in relevant research. In addition, Epstein-Barr virus (EBV), which has been detected in various tumors, such as Burkitt's lymphoma, EBV-associated gastric cancer, and nasopharyngeal carcinoma (NPC), 2 as well as pLELC, 5 either exists typically as an episome in cells or tends to integrate into the host genome.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing, that EBV is enumerated among human viruses with a proven role in oncogenesis, and the development of autoimmune disorders, as well as immunosuppression [40][41][42][43]. The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The latest literature search was performed in March 2021. Having carefully evaluated the extracted studies, we selected 42 relevant studies and the EBV status in LCs was summarized in Table 2 [ 12 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Presence Of Ebv In Lung Cancersmentioning
confidence: 99%
“…Indeed, elevated levels of multiple immune checkpoint molecules, such as indoleamine 2,4-dioxygenase (IDO), programmed cell death 1 (PD-1), cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), lymphocyte-activation gene 3 (LAG3), B and T lymphocyte attenuator (BTLA), and v-domain Ig suppressor of T cell activation (VISTA) were also detected in EBV(+) LCs [ 12 ]. Further, several studies have reported that high levels of programmed death-ligand 1 (PD-L1) were observed in EBV(+) LCs [ 64 , 66 ]. These immune inhibitors may contribute to EBV-associated tumor immune tolerance.…”
Section: Etiological Role Of Ebv In Lcmentioning
confidence: 99%